Structural and optical properties of Zn₁₋xCoxO thin films prepared by RF reactive sputtering technique - Savchuk, A.I.; Stolyarchuk, I.D.; Stefanuk, I.; Cieniek, B.; Sheregii, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We have reported the effect of Co doping on structural and optical properties of ZnO thin films prepared by the RF reactive sputtering technique. The composite targets were formed by mixing and pressing ZnO and CoO powders. The thin films were deposited on silica and glass substrates. The structures of samples have been studied by using X-ray diffraction (XRD) and atomic force microscopy (AFM). With the sensitivity of the XRD instruments, the structural analyses of Co-doped ZnO films reveal formation of predominant (002) reflection corresponding to the hexagonal wurtzite structure without any secondary phase. The AFM study showed that surface morphology of the Zn₁₋xCoxO films is composed of closely packed nanocrystallites with nanorod shape. The optical properties of the samples were studied using UV-vis absorption and PL spectra. The optical absorption spectra show a red shift of the band edge, which indicates that Co²⁺ ions substitute Zn²⁺ ions in ZnO lattice. In the room-temperature photoluminescence spectra, four main peaks were revealed in all the samples, which are attributed to ultraviolet, violet-blue, blue and green emission.